Temporal circuits and social triage in a Papua New Guinean Clinic. (March 2016) - Andersen, Barbara
This article examines how the temporalities generated by the "NGOization" of public health can lead to exclusionary forms of social and clinical triage. Through an ethnographic case study of a public–nongovernmental organization partnership HIV/STI clinic in the Highlands of Papua New Guinea, I discuss how ideas about the nature of nongovernmental institutions – as different from the long-established "government" and "church"/"mission" services – influence health workers' triage practices. By contextualizing this case study within broader ideological and material transformations in Papua New Guinea, I show how "NGO time" interfaces with other forms of temporality. I argue that local ideas about what nongovernmental organizations are, where they come from, and to whom they are accountable are essential to understanding how "NGO time" might lead to exclusionary practices. More broadly, I suggest that an ethnographic approach to the "nongovernmental" must first consider the local specificity of "government" as a cultural object.